Physicochemical properties and sensory acceptability of fermented roasted Robusta coffee (Coffea canephora L.) beans - Chan, Hao Yuan; Rukayadi, Yaya; Mohamad Azman, Ezzat; Ashari, Rozzamri; Abdul Halim Lim, Sarina (Institute for Research and Community Services, Institut Teknologi Bandung, 2024)
Spontaneous fermentation is becoming ever more elusive because of vast natural microbiota profiles that affect geographical region, climate, and applications of agrichemicals. This study aimed to identify the physicochemical and sensory properties of local planted (Serdang, Malaysia) Robusta (Coffea canephora L.) coffee beans after undergoing different spontaneous wet fermentation (SWF) periods i.e., 0 days as control, 3 days, and 5 days. The hardness decreased significantly (p < 0.05) by 80 to 90% in roasted fermented roasted Robusta coffee (FRRC) beans. The carbohydrate content was significantly higher (p < 0.05) at 9.4%, but protein and crude fibers were significantly (p < 0.05) lower at 31% and 9.7%, respectively. While the FRRC brew displayed deeper lightness (L*31.983), the FRRC powder displayed lighter lightness (L*49.553). The total soluble solid (TSS) was around 21% higher in FRRC and the water solubility index (WSI) had equivalent outcomes at about 8% higher in FRRC. Rheological analysis showed that the coffee fluid exhibited a shear-thickening property with fluid elastic components greater than viscosity. FRRC beans received higher ratings (score > 6) than non-FRRC beans (score between 5 and 6) in the consumer sensory evaluations.